SISTEM INFORMASI SIMPAN PINJAM KOPERASI KARYAWAN PTPN XII KEBUN SUMBER TENGAH - Chandra Amiliyani (Jurnal Ilmiah Informatika, 2018)
The saving and loan information system of the Employees Cooperative in PTPN XII (Persero) Kebun Sumber Tengah is an enterprise dealing with saving and loan particularly for the employees of PTPN XII (Persero) Kebun Sumber Tengah giving such a service for the members especially in saving and loan. The data management is already computerized even though it is still run by using Microsoft Office that it does make the members who want to do saving and loan should wait in longer time because it usually appears data redundancy in the saving and loan data itself. The researcher raises a problem based on what is faced in the saving and loan data management. It is then expected to help the cooperative staffs increase their service to the members as well as save the data or any important documents, so the information can be presented faster and more accurately.The method of developing the information system applies system developing tools such as Flow Map Context Diagram (Contex Diagram), DFD (Data Flow Diagram) and design tools while the database proposed is ERD (Entity Relationship Diagram) relation table. The saving and loan information system that is designed aims at building a computerized information system that can enable the employees in the cooperative department manage the data of member, data of saving, data of loan, and data of installment.